Analisis Laporan Keuangan Untuk Menilai Kinerja Di PT. Indoneisa Kenderaan Terminal,Tbk. Yang Terdaftar Di Bursa Efek Indoneisa Periode 2015-2019 - Syahputra, Heri Enjang (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This study aims todetermine and analyze in measuring the level of financial performance at PT. Indonesia Kendaraan Terminal Tbk, 2015-2019 period in terms of financial ratio analysis. Information on the level of financial performance is very important in maintaining the company's existence from competition. The analytical method used is descriptive method with a quantitative approach, with data collection techniques in the form of documentary research or Its kind, as well as data collection from the Indonesian Stock Exchange (BEI). The data analyzed were the financial statements of PT. Indonesia Kendaran Teminal Tbk. Namely the income statement and statement of financial position (BalanceSheet) for the period of 2015-2019. Assessment of the level of performance from the financial aspect uses financial ratio indicators, namely Current Ratio, Cash Ratio, Debt Ratio, Debt to Equity Ratio, Gross Profit Margin, Net Profit Margin, Return On Equity, Total Asset Turnover, Fixed Asset Turnover. Results of The research on the level of financial performance of PT. Indonesia Vehicle Terminal Tbk. Obtained a healthy predicate with the AA category consecutively during the period 2015 to 2019.